Religious freedom in a secular age a Christian case for liberty, equality, and secular government - Bird, Michael 1974- (Grand Rapids Zondervan Reflective, 2022)
"Religious Freedom in a Secular Age describes today's complicated debates about religious freedom, suggesting a way forward that neither privileges nor punishes religion. Tackling many complicated topics, this practical book encourages Christians to stand up for their faith in a way that is humble and gentle, yet also courageous"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Freedom Of Religion; Church and state; Secularization